Condom availability in New York City public high schools: relationships to condom use and sexual behavior. - Guttmacher, S (1997)
OBJECTIVES: This study examines the impact of the condom availability program in New York City public high schools by comparing rates of sexual activity and condom use for New York students and similar students in Chicago. METHODS: A total of 7119 students from 12 randomly selected New York schools and 5738 students from 10 Chicago schools participated in a cross-sectional survey. RESULTS: New York students, compared with Chicago students, reported equal rates of sexual activity but higher rates of condom use at last intercourse (odds ratio [OR] = 1.36). For higher-risk students (those with three or more sexual partners in the past 6 months), condom use was greater in New York (OR = 1.85) than in Chicago. CONCLUSIONS: Condom availability has a modest but significant effect on condom use and does not increase rates of sexual activity. These findings suggest that school-based condom availability can lower the risk of HIV and other sexually transmitted diseases for urban teenagers in the United States.